Social networks and access and utilization of weather and climate information: The case of upland farming communities in the Philippines - Aubrey D. Tabuga; Anna Jennifer L. Umlas; Katrina Mae C. Zuluaga; Sonny N. Domingo (Philippine Institute for Development Studies (PIDS), 2021)
Social norms and structures are vital factors that shape people's behavior and attitudes. It is, therefore, useful to analyze such underlying forces in the creation of strategies that are meant to influence behavior and activities. Agricultural extension services such as information dissemination and farmers' training are some of the interventions that can benefit from such analyses especially within a context of limited human and financial resources. The idea is to use the lessons learned from the analysis of social networks and norms in identifying potential local knowledge and information disseminators, thereby aiding the extension services. It also helps in the formulation of more contextualized approaches for reaching the underserved and hard-to-reach areas. Applying this approach, this study used the case of a remote upland area in Atok, Benguet, a major vegetable producer. This study used social network analysis to develop insights for designing more effective extension strategies. The results show that interventions like information and education campaigns can be improved by acknowledging the nuances in social relation structures.
Keywords: 330; social network analysis; information and education campaign; Philippines; Benguet farming; upland farming